Lean Manufacturing: Implementation, Opportunities and Challenges - Silva, Francisco (2019)
The paradigm of manufacturing is undergoing a major evolution throughout the world. The use of computers, the Internet and new challenges related to the Industry 4.0 have changed the way we engineer and manufacture products. Improving production with Lean Thinking is an evolution of a traditional approach in order to improve its processes to remain competitive in the global market. Lean Manufacturing is a multidimensional approach that embraces a wide variety of management practices in a unified system. These practices contain, quality systems, team work, and supplier management, among others. Nowadays, other practices have been adopted such as human factors and ergonomics. This book presents contributions of Lean Manufacturing applications in the world development and is intended to provide a comprehensive view of issues related to this area, with a specific focus on lean engineering principles; it is full of practical production examples of how Lean Thinking can be applied effectively to production systems. This work was conceptualized for an audience of graduate students mainly; however, it can also be consulted by engineers and company managers who seek state-of-the-art applications on Lean Manufacturing within a wide diversity of scenarios and conditions. The book, organized into 17 chapters, is intended to be an excellent source for dissemination of applied researches, lean concepts, and practices that have been successfully applied in the developing world domain. The book is also an excellent example of academy purpose with collaboration between different institutions from different countries that provide a global approach.